Knowledge and Practices of Adolescents about risk factors for Non-Communicable Diseases at Kabwohe Health Centre IV. - Dickson Agaba; Allan Muhumuza (Student's Journal of Health Research, 2021)
Background:  Non-communicable diseases (NCDS) are the leading cause of mortality and morbidity globally. Adolescents are involved in lifestyle behaviors that foster NCDs development later on in the future because of their lack of knowledge about NCDs risk factors. However, there is a paucity of studies that have dealt with knowledge and practices of adolescents about NCDs risk factors. This study therefore aimed at assessing the knowledge and practices of adolescents about NCDs risk factors at Kabwohe HCIV. Methods:  A health center-based cross-sectional study was conducted among 95 adolescents receiving health-related care services at Kabwohe health center IV. Information was collected using a structured questionnaire and analyzed using SPSS version 20. Descriptive statistics and bivariate analysis were used in the statistical interpretation. Results:  The overall knowledge of adolescents about NCDs risk factors was 60%. Concerning diet that has fruits, the majority 60(62.4%) took fruits at least once, twice or thrice in a week while 35(37.6%) took fruits more frequently as in four, five times or days as they are indicated in the table above. About vegetable intake,57(60%) percent took a diet with vegetables once, twice, or thrice in a week compared to the 38(40%) that took a diet with vegetables many times a week.44(35.8%) took sugary foods more often i.e. many times in a week compared to the 61(64.3%) that took them less often. The following variables were significantly associated with knowledge about NCDs risk factors: area of residence (p=.0028), Level of education (p=.0181). Conclusion:  Average levels of knowledge were recorded among adolescents receiving care at Kabwohe health center IV though there were high practicing percentages of the risky healthy lifestyle behaviors that foster NCDs development.